Mechanistic basis for potassium efflux-driven activation of the human NLRP1 inflammasome - Rozario, Pritisha (2024)
Nigericin, an ionophore derived from Streptomyces hygroscopicus, is arguably the most commonly used tool compound to study the NLRP3 inflammasome. Recent findings, however, showed that nigericin also activates the NLRP1 inflammasome in human keratinocytes. In this study, we resolve the mechanistic basis of nigericin-driven NLRP1 inflammasome activation. In multiple nonhematopoietic cell types, nigericin rapidly and specifically inhibits the elongation stage of the ribosome cycle by depleting cytosolic potassium ions. This activates the ribotoxic stress response (RSR) sensor kinase ZAKα, p38, and JNK, as well as the hyperphosphorylation of the NLRP1 linker domain. As a result, nigericin-induced pyroptosis in human keratinocytes is blocked by extracellular potassium supplementation, ZAKα knockout, or pharmacologic inhibitors of ZAKα and p38 kinase activities. By surveying a panel of ionophores, we show that electroneutrality of ion movement is essential to activate ZAKα-driven RSR and a greater extent of K+ depletion is necessary to activate ZAKα-NLRP1 than NLRP3. These findings resolve the mechanism by which nigericin activates NLRP1 in nonhematopoietic cell types and demonstrate an unexpected connection between RSR, perturbations of potassium ion flux, and innate immunity.